LA INVOCACIÓN A LA LUNA COMO MOTIVO ERÓTICO EN LA LITERATURA GRIEGA Y LATINA - Galán Vioque, Guillermo (Myrtia, 2004)
The moon traditionally presides over encounters between lovers. The connection between love and the moon is a universal commonplace. This article analyses the relationship between the moon and lovers in Greek and Latin literature, examines in detail the different invocations to the moon placed in the mouths of lovers, both those relating to the practise of magic and the purely literary, and defines the essential features of this literary motif.